EFFECT OF DESIGN PARAMETERS ON THE ULTIMATE STRENGTH AND COLLAPSE BEHAVIOUR OF STIFFENED PANELS - Hanif, Muhammad Imaduddin; Adiputra, Ristiyanto; Prabowo, Aditya Rio; Muhayat, Nurul; Marta, Adnan Sandy Dwi; Huda, Nurul; Carvalho, Hermes (Journal of Applied Engineering Science, 2023)
Research about stiffened panel applications in ships has massively progressed with the amount of several methods to analyze it. Various studies had been conducted on stiffened panels using Finite Element Method (FEM). However, none have thoroughly explored the most optimal and efficient analysis methods and settings. Given the growing importance of FEM in reliability analysis for ship structures, particularly stiffened panels, a comprehensive study comparing different approaches is of paramount significance. Such research would not only streamline time-consuming procedures but also offer invaluable recommendations to advance the field's understanding and practical applications. In this paper, a finite element analysis study was done to analyze the influence of several parameter modeling of stiffened panels not only to achieve the models' ultimate strength value and collapse behavior but also to offer practical recommendations on the most optimal and efficient methods for analyzing stiffened panels through FEM. Conducting modification of three variations of the model configuration, four variations of boundary condition, and four variations of transverse stiffener modeling to compare each other. Running time consumed when simulations are calculated in ANSYS APDL was also being considered. The results showed a significant difference in modifying the model configuration's case, while in contrast, the modification of boundary conditions and transverse stiffener modeling only showed a slight difference in ultimate strength value. In addition, modification of transverse stiffener geometry only gave the difference by around 0.5 MPa. The model configuration case (A1 v A2) showed the most remarkable running time difference, which reached six times difference.
Keywords: stiffened panel, model configuration, boundary condition, transverse stiffener modelling, finite element method